Mali: safe heaven to terrorist? - Besenyő, János (Terrorism and political contention, 2024)
Mali, or officially the Republic of Mali, is a West African state, the second largest country in the region; until 1960 it was a colony of France under the name French Sudan. Mali has a specific geopolitical and migration context, given its proximity to neighboring unstable areas in the region, its highly vulnerable environment to climate change and food insecurity, and its historical migration routes. Mali's population is particularly at risk of violence, exploitation, and abuse related to recruitment into armed groups. On the security front, unidentified armed groups are increasingly carrying out violent and deadly attacks on civilians, often taking advantage of existing inter- and intra-community conflicts. During 2022, various Islamist armed groups linked to the Islamic State of Greater Sahara (ISGS) and Al-Qaeda expanded their attacks in southwestern Mali and the capital, Bamako, killing hundreds of civilians. Relations between Mali and France have deteriorated. Mali expelled the French ambassador after France's foreign minister questioned the legitimacy of the transitional government. The deployment at the end of 2021 of the Russian Wagner Group, classified as a “military trainer” by the Malian government, and the subsequent accusation of atrocities against them and the Malian security forces provoked sharp condemnation among Mali's foreign partners. Chaos and uncertainty favor terrorist groups. Political instability and an unsettled domestic political situation are a safe haven for terrorist groups. To eradicate this, political and economic stability, as well as cooperation with key international actors would be necessary.